Desenvolvimento de métodos para determinação de compostos voláteis e cera cuticular de maçãs e a aplicação no armazenamento em atmosfera controlada dinâmica - Klein, Bruna (2016)
Volatile organic compounds (VOCs) and cuticular apple wax profiles are important quality attributes, which are closely related to aroma/flavor. In this sense, the determination of these fractions during the storage can to provide relevant information on the main metabolic pathways stimulated during the storage. Nowadays there is a lack of methods that enable sustainable characterization of these fractions, fulfilling the green chemistry requirements. Thus, the objective of this study were: Article 1 – to determine experimental conditions for volatile compounds extraction from apple headspace, by solid-phase microextraction, using the Response Surface Methodology in order to assist in the time, temperature and salting out effects, as well as the application of the method for the assessment of volatile profile changes of two apples during dynamic controlled atmosphere storage by respiratory quotient technique at the level 1.3 (ACD-QR 1,3). Article 2 – to develop and to apply a method for the extraction of cuticular apple waxes, using the homogeneous liquid-liquid extraction (HLLE) method, assessing type and volume of extractor and disperser solvents, ionic strength and homogenization procedure. In the SPME method, the best extraction conditions have corresponded to 77-minutes extraction at 40 ºC, with addition of 30% (m/v) NaCl. Regarding the volatile compound extraction, the purposed method has been efficient, allowing the determination of different important substances to apple odor/aroma during storage. In general, there has been reduction in esters production along the storage time, in contrast to the alcohols and aldehydes increased. For the cuticular waxes extraction, the best extraction yields have been obtained in the following conditions: 10 cm² of homogenized fruit epidermis in 5 mL distilled water; 4 mL organic solvent (chloroform), divided into three successive extractions; 4 mL dispersant solvent (acetone); vortexing for 2 minutes. The purposed method has allowed an extraction higher than 95% of the total wax content and it has presented an adequate precision <3%. Thirty-two compounds have been identified, including acids, fatty acids, hydrocarbons, sterol acids, sterols, terpenes, among others. Fatty acids have been the major constituents in the analyzed extracts. The compounds nonacosane and ursolic acid have also significantly contributed to the studied fractions. The HLLE method has answered satisfactorily the qualitative and quantitative characterization of the epicuticular apple wax components.